Leveraging AI tools for streamlined library event planning: a case study from Lane Medical Library - Boglarka Huddleston; Colleen Cuddy (Journal of the Medical Library Association)
Health sciences and hospital libraries often face challenges in planning and organizing events due to limited resources and staff. At Stanford School of Medicine’s Lane Library, librarians turned to artificial intelligence (AI) tools to address this issue and successfully manage various events, from small workshops to larger, more complex conferences. This article presents a case study on how to effectively integrate generative AI tools into the event planning process, improving efficiency and freeing staff to focus on higher-level tasks.